The ‘very moment’ when UDG recognizes a flipped-out uracil base in dsDNA - Vinnarasi Saravanan; Nessim Raouraoua; Guillaume Brysbaert; Stefano Giordano; Marc F. Lensink; Fabrizio Cleri; Ralf Blossey (Scientific Reports, 2025)
Abstract Uracil-DNA glycosylase (UDG) is the first enzyme in the base-excision repair (BER) pathway, acting on uracil bases in DNA. How UDG finds its targets has not been conclusively resolved yet. Based on available structural and other experimental evidence, two possible pathways are under discussion. In one, the action of UDG on the DNA bases is believed to follow a ‘pinch-push-pull’ model, in which UDG generates the base-flip in an active manner. A second scenario is based on the exploitation of bases flipping out thermally from the DNA. Recent molecular dynamics (MD) studies of DNA in trinucleosome arrays have shown that base-flipping can be readily induced by the action of mechanical forces on DNA alone. This alternative mechanism could possibly enhance the probability for the second scenario of UDG-uracil interaction via the formation of a recognition complex of UDG with flipped-out base. In this work, we describe DNA structures with flipped-out uracil bases generated by MD simulations which we then subject to docking simulations with the UDG enzyme. Our results for the UDG-uracil recognition complex support the view that base-flipping induced by DNA mechanics can be a relevant mechanism of uracil base recognition by the UDG glycosylase in chromatin.